2021
DOI: 10.1186/s12967-021-02784-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of opioids in cancer response to immunotherapy

Abstract: Background The response to immunotherapy can be impaired by several factors including external intervention such as drug interactions with immune system. We aimed to examine the immunomodulatory action of opioids, since immune cells express opioid receptors able to negatively influence their activities. Methods This observational, multicenter, retrospective study, recruited patients with different metastatic solid tumors, who have received immunoth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 61 publications
1
27
0
Order By: Relevance
“…This study showed that opioid use was negatively associated with thyroid-related complications in patients treated with PD-1/PD-L1 inhibitors. Opioids play a crucial role in increasing the resistance to immunotherapy [29]. Morphine and buprenorphine reduce the levels of interleukin-4 mRNA and protein in T cells [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that opioid use was negatively associated with thyroid-related complications in patients treated with PD-1/PD-L1 inhibitors. Opioids play a crucial role in increasing the resistance to immunotherapy [29]. Morphine and buprenorphine reduce the levels of interleukin-4 mRNA and protein in T cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…Morphine and buprenorphine reduce the levels of interleukin-4 mRNA and protein in T cells [30]. A retrospective study on 102 cancer patients administered opioids and ICIs showed poor outcomes [31], possibly because of the presence of opioid receptors on immune cells [29]. As opioid receptors are expressed in immune cells, opioids could alter immune responses [32].…”
Section: Discussionmentioning
confidence: 99%
“…We too read with interest the article “The Role of Opioids in Cancer Response to Immunotherapy” by Botticelli et al, which suggests that opioids impair the immune response to cancer in patients receiving immunotherapy [ 1 ].…”
Section: Dear Editormentioning
confidence: 99%
“…In the Results section, the authors state: “ …opioids use was significantly higher in patients affected by NSCLC [Non-Small Cell Lung Cancer] (p < 0.0001), in patients with a worse ECOG PS [Eastern Cooperative Oncology Group Performance Status] (p < 0.0001), in second-line setting subgroup (p = 0.009), in patients taking corticosteroids (p < 0.0001), and in patients with a high tumor burden (p = 0.006) ” [ 1 ].…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation